Effect of intragastric pH on antral gastrin and somatostatin release in anaesthetised, atropinised duodenal ulcer patients and controls. Issue 2 (February 1987) - Jensen, S L; Holst, J J; Christiansen, L A; Shokouh-Amiri, M H; Lorentsen, M; Beck, H; Jensen, H E
Abstract : The synchronous change in the antral release of gastrin and somatostatin into a vein draining the stomach was studied during acidic and alkaline intragastric pH in six anaesthetised duodenal ulcer patients and six controls after atropinisation. No differences in the basal secretion of gastrin and somatostatin were observed among the two groups. Alkaline as well as acidic intragastric pH had no effect on the antral release of somatostatin in duodenal ulcer patients and controls. In contrast, alkaline intragastric pH was associated with a significantly higher antral gastrin release in duodenal ulcer patients than in controls. Acidic intragastric pH was associated with a significantly smaller inhibition of antral gastrin release in duodenal ulcer patients than in controls. These results suggest that atropinised anaesthetised duodenal patients release gastrin abnormally in the presence of acidic or alkaline intragastric pH and that any inverse relationship between antral gastrin and somatostatin release is uncoupled under these conditions.